ANALISIS HUBUNGAN KAUSAL BELANJA DAERAH, JUMLAH PENDUDUK, DAN PENDAPATAN ASLI DAERAH: STUDI PADA KABUPATEN/KOTA DI JAWA BARAT - Burhany, Dian Imanina; Fauziah, Rachma Syalwa (Accounting Department, Politeknik Negeri Bandung, 2025)
This study aims to analyze the causal relationship between regional expenditure (employee expenditure and capital expenditure), population, and regional original income (PAD) in 27 regencies/cities in West Java. The background of the study is based on the still low regional fiscal independence in West Java, which is reflected in the high dependence on central transfer funds and the downward trend in PAD realization in several regions during the 2019-2023 period. With a quantitative approach, this study utilizes secondary data on the realization of the 2019-2023 Regional Budget (APBD) from the Directorate General of Fiscal Balance, as well as population data from the Central Statistics Agency. Data analysis employs multiple linear regression and hypothesis testing, including t-test and F-test, to examine the effect of the independent variables—regional expenditure and population—on the dependent variable PAD, utilizing the SPSS 26 application. The study results show that both types of regional expenditure, namely employee expenditure and capital expenditure, have a positive and significant effect on PAD. However, population does not have a significant effect on PAD. Simultaneously, employee expenditure, capital expenditure, and population have a significant effect on PAD.